2009
DOI: 10.1051/0004-6361/200810421
|View full text |Cite
|
Sign up to set email alerts
|

The nature of $\ion{N}{v}$ absorbers at high redshift

Abstract: Aims. We present a study of N v absorption systems at 1.5 z 2.5 in the spectra of 19 QSOs, based on data obtained with the VLT/UVES instrument. Our analysis includes both the absorbers arising from the intergalactic medium, as well as systems in the vicinity of the background quasar. Methods. We construct detailed photoionization models to study the physical conditions and abundances in the absorbers and to constrain the spectral hardness of the ionizing radiation.Results. The rate of incidence for intervening… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 106 publications
(185 reference statements)
0
41
0
Order By: Relevance
“…(a) the median N v line width in DLAs b = 18 km s −1 is three times broader than the median reported by Fechner & Richter (2009) in the (photoionized) IGM; (b) collisional ionization models for plasma at log T = 5.2−5.4 can reproduce (when corrected for the non-solar elemental abundance ratios present in DLAs) the observed integrated high-ion column density ratios in the majority of DLAs in our sample; (c) there is no evidence for an enhanced N v detection rate in DLAs between 500 and 5000 km s −1 from the QSO, as would be expected if the N v was predominantly photoionized. 7.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…(a) the median N v line width in DLAs b = 18 km s −1 is three times broader than the median reported by Fechner & Richter (2009) in the (photoionized) IGM; (b) collisional ionization models for plasma at log T = 5.2−5.4 can reproduce (when corrected for the non-solar elemental abundance ratios present in DLAs) the observed integrated high-ion column density ratios in the majority of DLAs in our sample; (c) there is no evidence for an enhanced N v detection rate in DLAs between 500 and 5000 km s −1 from the QSO, as would be expected if the N v was predominantly photoionized. 7.…”
Section: Discussionmentioning
confidence: 65%
“…High-redshift (z ≈ 2−3) N v absorption is found in several environments, including the intergalactic medium (Bergeron et al 2002;Carswell et al 2002;Simcoe et al 2002;Boksenberg et al 2003;Simcoe et al 2006;Schaye et al 2007;Fechner & Richter 2009), quasar-intrinsic or "associated" systems (Hamann 1997;Petitjean & Srianand 1999;D'Odorico et al 2004;Fechner et al 2004;Fechner & Richter 2009;Fox et al 2008a), LBGs (Pettini et al 2002b;Shapley et al 2003), and gamma-ray burst (GRB) host galaxies (Prochaska et al 2008c;Fox et al 2008b;7 Whether or not the H ii columns derived from N v and O vi should be summed depends on whether the two lines trace the same regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon -Previous studies of intervening absorbers with achievable carbon measurements have observed an underabundance of carbon compared to α-elements (Fechner & Richter 2009;Pettini et al 2008;Erni et al 2006;Richter et al 2005). This is expected from modelling (e.g.…”
Section: Abundances From Ion Ratiosmentioning
confidence: 86%